Hydrogen-bond transition from the vibration mode of ordinary water to the (H, Na)I hydration states : molecular interactions and solution viscosity - Zhou, Yong (2019)
With the aid of differential phonon spectrometrics (DPS) and surface stress detection, we show that HI and NaI solvation transforms different fractions of the HO stretching phonons from the mode of ordinary water centred at ∼3200 to the mode of hydration shell at ∼3500 cm−1. Observations suggest that an addition of the H ↔ H anti-hydrogen-bond to the Zundel notion, [H(H2O)2]+, would be necessary as the HO bond due H3O+ has a 4.0 eV energy, and the H ↔ H fragilization disrupts the solution network and the surface stress. The I− and Na+ ions form each a charge centre that aligns, stretches, and polarize the O:HO bond, resulting in shortening the HO bond and its phonon blue shift in the hydration shell or at the solute-solvent interface. The solute capabilities of bond-number-fraction transition follow: fH = 0, fNa ∝ C, and fI ∝ 1 − exp(−C/C0) toward saturation, with C being the solute molar concentration and C0 the decay constant. The fH = 0 evidences the non-polarizability of the H+ because of the H ↔ H formation. The linear fNa(C) suggests the invariance of the Na+ hydration shell size because of the fully-screened cationic potential by the H2O dipoles in the hydration shell but the nonlinear fI(C) fingerprints the I− ↔ I− interactions at higher concentrations. Concentration trend consistency between Jones–Dole’s viscosity and the fNaI(C) coefficient may evidence the same polarization origin of the solution viscosity and surface stress.